English Communication Skill: Styles, Strategies and Empowerment of the Teacher: Exploring the Strategies and Impact of English Communication Skill in Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Learning styles and strategies differ from one to another. They are acquired only through practice and experience. The proper understanding and recognition of styles and strategies help us to improve the quality of learning. Learning styles are of different kinds. Environmental factors also determine the qualitative learning. School education is entirely different from college education. Teachers painstakingly explain, read out the text and ask questions to check understanding at schools. At college, the teacher no longer occupies the centre stage because lecture method is adopted. A learner ought to go beyond the lecture to purse learning. A learner adopts new learning skills and techniques for better understanding of hisher subject. Such learning styles and strategies make the students more active learners.The 21st century learner is a smart learner. Various theories and principles of language learning and language acquisition have been propounded over the past few centuries. It has resulted numerous approaches and practices ranging from structural approaches to communicative approaches. There is a huge gulf between linguistic competence and practices of the ESL students in India.In the backdrop of the present scenario of learning English as a second language, teachers play a strategic role in English classrooms. Teaching strategy in acquisition of learning English language is a matter of concern of English teachers across the country. The teachers are in quest of teaching methodologies to make it innovative and critical. As a result, the student can face the challenges of life through sound and convincing English communication skill.Communication is an artistic job. It enhances the power, authority and challenge of life. Life is pleasant and awesome with an excellent, enjoyable English communication skill. Language is the greatest achievement of human intelligence and the best means of communication. Effective communication elevates one to an honorable height in the society. It is fundamental attribute of cultural identity and empowerment, both for the individual and group. English language as a tool of communication is an effective means of exerting and exercising power and prominence. Power is nothing but a strategy (Michel Foucault) A teacher is effective and successful only if heshe knows how to communicate his ideas to the students effectively and strategically. The best teaching style and strategy depends on conception of masterly ideas and resourceful expression of ideas. Communication is a supreme art for English teachers living in the age of privatization, liberalization and globalization. Why does communication fail. How should we communicate. Why should we communicate. Who should we communicate. How will communication help the teacher community in intellectual, social, economic and political advancement and empowerment. The present paper is an in-depth analysis of all these pertinent issues in connection to the teacher empowerment.